Characterization of the input material quality for the production of tisagenlecleucel by multiparameter flow cytometry and its relation to the clinical outcome - Martin Štach; Martin Štach; Robert Pytlík; Robert Pytlík; Kristýna Šmilauerová; Kristýna Šmilauerová; Jana Rychlá; Martin Mucha; Martin Mucha; Jan Musil; Abhishek Koladiya; Matěj Nemec; et al. (Pathology and Oncology Research, 2023)
Tisagenlecleucel (tisa-cel) is a CD19-specific CAR-T cell product approved for the treatment of relapsed/refractory (r/r) DLBCL or B-ALL. We have followed a group of patients diagnosed with childhood B-ALL (n = 5), adult B-ALL (n = 2), and DLBCL (n = 25) who were treated with tisa-cel under non-clinical trial conditions. The goal was to determine how the intensive pretreatment of patients affects the produced CAR-T cells, their in vivo expansion, and the outcome of the therapy. Multiparametric flow cytometry was used to analyze the material used for manufacturing CAR-T cells (apheresis), the CAR-T cell product itself, and blood samples obtained at three timepoints after administration. We present the analysis of memory phenotype of CD4/CD8 CAR-T lymphocytes (CD45RA, CD62L, CD27, CD28) and the expression of inhibitory receptors (PD-1, TIGIT). In addition, we show its relation to the patients’ clinical characteristics, such as tumor burden and sensitivity to prior therapies. Patients who responded to therapy had a higher percentage of CD8+CD45RA+CD27+ T cells in the apheresis, although not in the produced CAR-Ts. Patients with primary refractory aggressive B-cell lymphomas had the poorest outcomes which was characterized by undetectable CAR-T cell expansion in vivo. No clear correlation of the outcome with the immunophenotypes of CAR-Ts was observed. Our results suggest that an important parameter predicting therapy efficacy is CAR-Ts’ level of expansion in vivo but not the immunophenotype. After CAR-T cells’ administration, measurements at several timepoints accurately detect their proliferation intensity in vivo. The outcome of CAR-T cell therapy largely depends on biological characteristics of the tumors rather than on the immunophenotype of produced CAR-Ts.